2011
DOI: 10.1016/s1674-8301(11)60019-5
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of NP11-4-derived immunotoxin scFv-artesunate in reducing hepatic fibrosis induced by Schistosoma japonicum in mice

Abstract: Schistosomiasis is one of the most prevalent parasitic diseases in China, and hepatic fibrosis caused by schistosome infection is the principal cause of death. The aim of this study was to evaluate the efficacy of NP11-4-derived immunotoxin scFv-artesunate on Schistosoma japonicum-induced hepatic fibrosis. A single-chain variable fragment (scFv) was generated from the murine anti-Schistosoma japonicum (S. japanicum) monoclonal antibody NP11-4. The scFv was expressed as a soluble protein and purified by Ni-affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These include modulating immune responses: such as preventing graft versus host disease [33,34], removing T-cells from grafts [35,36] or the elimination T-regulatory cells [37,38,39,40]. Some progress has been made also in producing immunotoxins with anti-viral [41,42,43] or anti-parasitic activity [44]. Ex-vivo uses are also anticipated whereby unwanted cells are killed before infusing bone marrow or other stem cell like preparations [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…These include modulating immune responses: such as preventing graft versus host disease [33,34], removing T-cells from grafts [35,36] or the elimination T-regulatory cells [37,38,39,40]. Some progress has been made also in producing immunotoxins with anti-viral [41,42,43] or anti-parasitic activity [44]. Ex-vivo uses are also anticipated whereby unwanted cells are killed before infusing bone marrow or other stem cell like preparations [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a previous study demonstrated that artesunate conjugated with a single-chain variable fragment from the monoclonal antibody NP11-4 inhibited liver fibrosis induced by schistosomiasis (14). Therefore, it was hypothesized that artesunate may attenuate pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyproline content in the four groups at different time points (µg/g) At 7,14,21. and 28 days after bleomycin injection with or without artesunate treatment, rats were exsanguinated and their lungs were removed.…”
mentioning
confidence: 99%
“…Artesunate is a kind of artemisinin derivatives, which is a traditional Chinese medicine widely used as anti malaria drugs.Artesunate has good water solubility and high oral bioavailability, so it has good pharmacological effect [11].Recent studies have found that,Artemisinin, a long-term anti malaria drug, has been proved to have antioxidant, anti-in ammatory, anti apoptotic and anti proliferative effects, making it a therapeutic option for eye diseases [11,12].Studies have shown that artesunate can inhibit the proliferation of human ovarian cancer cells and TGF-β [13].However, its preventive effect on RPE cells is not clear.…”
Section: Introductionmentioning
confidence: 99%